Evaluation of Central Nervous System Tuberculomas by Using Modern Diagnostic Techniques - Ubaid Ullah, Safia Bano, Shoaib Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess central nervous system tuberculomas by using modern MRI techniques such as Diffusion MRI (dMRI), Nuclear magnetic resonance spectroscopy (NMR spectroscopy) and BOLD venographic imaging. Study design: A retrospective study design Study setting: From 5th Feb 2021 to 5th Feb 2022 at the department of Neurology of Ibe-e-Siena Hospital, Multan. Methods: A retrospective study was conducted in the neurology department of Ibe-e-Siena Hospital & Research Institute Multan from 5th February 2021 to 5th February 2022. A total of 100 patients with suspected intracranial tuberculomas were included in the study. Advanced MRI techniques, including Diffusion MRI (dMRI), Nuclear magnetic resonance spectroscopy (NMR spectroscopy) and BOLD venographic imaging and conventional MRI, was performed on the patients. The study was approved by the ethical committee of the hospital, and all the patients provided their written consent for inclusion in the study Results: NMR spectroscopy evaluation showed that N-acetylaspartate /Creatine and N-acetylaspartate /Choline ratios of tuberculomas did not differ significantly from malignant brain lesions (p>0.04). But the malignant brain lesion (2.59) were significantly higher than the Choline/Creatine ratio of tuberculomas(1.29). BOLD venographic imaging evaluation showed no hypointense peripheral ring in malignant brain lesions but showed complete and regular rings in 36 (58.1%) of tuberculomas. Conclusion: Diffusion MRI did not help distinguish tuberculomas from metastasis and gliomas. However, NMR spectroscopy did offer this advantage by evaluating their unique metabolite pattern. BOLD venographic imaging showed the presence of a complete peripheral hypointense ring helping in diagnosing tuberculomas